A review on emerging pathogenic bacteria in marine environment - Mollika, Faria Sultana; Mahfuz-Un-Nesa (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2021.